Estimasi Karbon Tersimpan dalam Tumbuhan Bundung Besar (Scirpus compressus) dari Rawa Lebak - Muhammad Arsyad Ghani; Krisdianto Krisdianto (Bioscientiae, 2021)
The contents of absolute in biomassa or  values of carbon which kept in a wide coalescence is carbon storage.  A valley swamp is a swampland which has influenced by rainwater, either rainwater at local area or around area and headwaters the purpose of this research is to get information about carbon which consist in Bundung Besar (Scirpus compressus).  Determination of the research location will use purposive sampling. The location of plant sampel removal held four location and each location divided into two stations, therefore therewere eight monitoring stations with terrace-space 1x1 m2.  The location of plant sampel is at subdistrict Tungkaran, subdistrict Sungai Tabuk, and subdistrict Bati-Bati. The measurement of carbon in bundung besar used Walkey and Balck method.  The data will analyze with statistic non parametric and the difference of carbon in each station will analyze with cluster method.  The result indicate the measurement of organic carbon in Bundung besar for each station is variably the variably of each station is around 772,651-3042,337 g/m2.  The highest result at station 6 (Tungkaran Village) and the losest at station 2 (Pandahan  Village).